Individuals and small groups in jewish resistance to the holocaust : a case study of a young couple and their friends - Braber, Ben (Anthem Press, 2022)
This book aims to increase our knowledge and deepen the understanding of Jewish resistance to the Holocaust by examining personal circumstances and characteristics of Jewish resistance members and the formation of small Jewish resistance groups.